The State of Specific Immunity to Measles and Rubella Virus in Newborns and their mothers - N. T. Tikhonova; O. V. Tsvirkun; A. G. Gerasimova; A. A. Basov; R. A. Frolov; E. B. Ezhlova; A. A. Melnikova; A. A. Vatolina; N. Yu. Ivannikov; T. N. Melnik; A. I. Zakharyan (Эпидемиология и вакцинопрофилактика, 2017)
Objective: evaluate the passive specific immunity to measles and rubella in newborns and their mothers. Materials and metods: a study was made by the ELISA of the state of specific immunity to measles and rubella in 226 puerperas aged 15 to 44 without taking into account the vaccination status and their newborns in maternity hospitals in Moscow and Moscow Region. Results - the seropositive of measles proportion - 73.9 ± 2.9%, the rubella - 84.5 ± 2.4%. Comparison of the results of the study of immunity to rubella in puerperas and newborns with the results of previous years did not reveal any significant differences. The results of the examination of 226 newborns for the presence of antibodies to the rubella virus showed that the proportion of seropositive measles to the virus turned out to be 177 (78.3 ± 2.7%) children, rubella - 83.6 ± 2.4%, comparable to results of a survey of their mothers. Conclusion: high level of protection of the puerperas and their newborns from these infections. However, the organization and carrying out of vaccinations requires increased attention and control, since only high and timely coverage with vaccinations will prevent the increase in the incidence of infection when meeting with the pathogen of infection, including children of the first year of life.